Diagnóstico del nivel de integración y madurez del sistema de gestión de una empresa comercializadora del sector aseo y cosméticos (2020)
This article presents the results of the diagnosis of the level of integration and maturity of the management system of a marketing company in the cleaning and cosmetics sector belonging to the food chain, as a preliminary step to the proposal of an integrated management system based on the regulatory references NTC-ISO 9001:2015, NTC-ISO 14001:2015, Decree 1072/2015 and NTC-ISO 22000:2018, through the application of different instruments/tools to measure management systems maturity. The data collected in parallel are triangulated through correlation with the organizational strategic analysis to determine 21 key variables of priority intervention to advance in the short term in the level of maturity and integration of the management system of the organization under study. Also, the results obtained allow to confirm the strategy and guide the approach of the integration process.